Analysis of Color Quality Difference of Liupao Tea Infusion - Hongfei XIAO; Hao XU; Xingchang OU; Huimin AN; Jian'an HUANG; Zhonghua LIU (Shipin gongye ke-ji)
The color of the tea infusion is an important factor in evaluating the quality of tea. The objective of this research was to investigate the correlation between the color quality of the infusion and the chemical composition of Liupao tea. Sensory evaluation and color difference analysis were employed to differentiate the infusion color of Liupao tea. The components of Liupao tea were quantified using ultraviolet spectrophotometry and ultra performance liquid chromatography coupled with quadrupole orbitrap mass spectrometry (UPLC-Q-Orbitrap-MS). Furthermore, multivariate statistical analysis was utilized to examine the relationship between these components and the infusion color. The infusion coloration of Liupao tea could be categorized into three distinct types: Orange-red, red, and intense red. Notably, the concentration of theabrownin varied significantly among these three categories of tea infusion (P<0.05). A total of 120 compounds were identified in Liupao tea samples, and the concentrations of amino acids, catechins, phenolic acids, flavonoids exhibited significant variations among the three categories of infusion color (P<0.05). The 28 major nonvolatile components were identified based on the VIP values, which included N-acetyl-DL-glutamic acid, 4-keto-L-proline, catechin, epicatechin, catechin gallate, epigallocatechin gallate, rutin, quercetin, isoquercetin, dihydromyricetin, myricetin-3-O-galactopyranoside, quinic acid, gallic acid, and 3-galloyl quinic acid. It was observed that the content of these compounds diminished as the infusion color intensified. This research offers a theoretical framework for understanding the material foundations of infusion coloration and the mechanisms underlying the quality characteristics of Liupao tea.